2017
DOI: 10.1002/rth2.12030
|View full text |Cite
|
Sign up to set email alerts
|

Principles and theory guiding development and delivery of patient education in disorders of thrombosis and hemostasis: Reviewing the current literature

Abstract: Essentials Appropriate, theory‐based education has been linked to improved patient and system outcomes.Literature regarding theory‐based education in thrombosis and hemostasis is extremely limited.Current literature describes teaching strategy in single centers vs. impact of underlying theory.Collaborative efforts are required to make recommendations regarding optimization of education. Prior work regarding patient education has identified the importance of using learning theory and educational models to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Substantial gaps in research evidence relating to ICT programs delivered in the community health setting by health professionals were identified. There were few co-designed ICT programs (and no documentation of co-design processes) and no reference to specific pedagogical or andragogical educational principles guiding program delivery-gaps identified by other reviews [166,167]. Engaging stakeholders in program development through co-design processes is thought to create programs that are more useful and acceptable to end users [168].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Substantial gaps in research evidence relating to ICT programs delivered in the community health setting by health professionals were identified. There were few co-designed ICT programs (and no documentation of co-design processes) and no reference to specific pedagogical or andragogical educational principles guiding program delivery-gaps identified by other reviews [166,167]. Engaging stakeholders in program development through co-design processes is thought to create programs that are more useful and acceptable to end users [168].…”
Section: Principal Findingsmentioning
confidence: 99%
“…The aim of patient education is to enable ‘individuals to make informed decisions about their personal health‐related behaviour’ 18 . Several educational theories have provided a framework of patient education, but defining the optimal content components, appropriate format, timing and duration is still an unmet goal in OAC patient education 19 …”
Section: Introductionmentioning
confidence: 99%
“…18 Several educational theories have provided a framework of patient education, but defining the optimal content components, appropriate format, timing and duration is still an unmet goal in OAC patient education. 19 One valid method of exploring important aspects of optimal patient education is to use qualitative research methods to seek input from key stakeholders. To inform our randomized controlled trial evaluating the coordination of OAC management early posthospital discharge in adults (NCT02777047), we conducted focus groups on barriers and facilitators to optimising oral anticoagulant therapy management.…”
Section: Introductionmentioning
confidence: 99%
“…7 Additionally, developers of educational interventions rarely incorporate any learning theories or strategies when creating their tools or testing their effectiveness. 8…”
Section: Introductionmentioning
confidence: 99%
“…Clinical education that has implemented them into their development have shown improved clinical outcomes. However, a systematic review of thrombosis and hemostasis education found that only two studies (one in pediatrics, one in adults) out of 16 incorporated learning theories into their patient education 8. Those that did incorporate learning theories in their development didn't measure outcomes that would lead to conclusions about whether learning based education is better or worse.…”
mentioning
confidence: 99%